Pengaruh Brand Image, Korean Wave, Fanatisme dan Brand Ambassador terhadap Keputusan Pembelian - Indah Wardani; Rizky Dermawan (Universitas Batanghari Jambi, 2023)
Instant noodles are one of the fast food that is popular with the public because it has a delicious taste, is practical and quickly served at an economical price. This study aims to examine and determine the effect of brand image, korean wave, fanaticism and brand ambassadors on purchasing decisions of NCT Dream edition of Lemonilo noodles. The research method used is quantitative method. The sampling method used is non-probability sampling with purposive sampling technique. Respondents in this study were 100 consumers of Lemonilo instant noodles fans of NCT Dream who followed the Instagram account @wownctzen.id. The data collection technique used was primary data in the form of a questionnaire with a Likert scale, and secondary data in the form of literature and previous research. The data analysis technique uses SEM-PLS with the help of the smartPLS application. The results of the study show that brand image, Korean wave, fanaticism and brand ambassadors have a positive and significant influence on purchasing decisions for consumers of NCT Dream Lemonilo noodles.